Food security: The global food system under radical change - Stordalen, Gunhild; Fan, Shenggen (International Food Policy Research Institute, 2018)
Food systems have been central to recent unprecedented reductions in global poverty, hunger, and undernutrition, and will be the foundation of future progress. Yet food is among the leading causes of our global health and sustainability crises. Efforts to sustainably end hunger and malnutrition will depend on reshaping our food systems. Radical global changes, including rising antiglobalization sentiment and emerging technologies both inside and outside the agriculture sector, are creating new challenges and opportunities. How these global trends are managed will be crucial for ensuring that food systems can deliver sufficient nutritious, affordable, and healthy food for all within the sustainability parameters of the planet.